2018
DOI: 10.1515/rjim-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coronary risk factors and angiographic findings in younger and older patients with significant coronary artery disease

Abstract: Background: Coronary artery disease (CAD) is uncommon among young adults and may

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(18 reference statements)
1
6
0
1
Order By: Relevance
“…Furthermore, positive correlations between IL-6 and markers of atherosclerosis were mainly observed in patients older than ours. Carotid IMC thickness positively correlates with advancing atherosclerotic lesions in coronary arteries [49] that are usually less extensive in young patients than older ones [50]. However, we demonstrated the negative correlation of IL-6 level with diameter of ascending aorta.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, positive correlations between IL-6 and markers of atherosclerosis were mainly observed in patients older than ours. Carotid IMC thickness positively correlates with advancing atherosclerotic lesions in coronary arteries [49] that are usually less extensive in young patients than older ones [50]. However, we demonstrated the negative correlation of IL-6 level with diameter of ascending aorta.…”
Section: Discussionmentioning
confidence: 48%
“…The mechanisms of MI in young individuals seem to differ significantly from those affecting older patients and could be grouped into three main categories: 1) atherosclerotic coronary artery disease; 2) non-atherosclerotic ischaemic heart disease; 3) hypercoagulable state. The individual's genetic profile contributes, together with other predisposing factors, to create a favorable milieu for the development of atherosclerosis and MI at a younger age 11 (Figure 1). This review article discusses the main differences that exist between the younger and elderly MI patients in the four different categories mentioned above.…”
Section: Cad Mainly Affects Older Individuals As Shown In the Landmar...mentioning
confidence: 99%
“…The left anterior descending (LAD) is the most commonly affected artery in both patient groups. Younger patients frequently present with single-vessel CAD 12,13 , fewer coronary lesions 12 and lower lesion complexity, as estimated by the Gensini score 11 which is a strong predictor of successful restoration of myocardial perfusion 14 as well as short and long-term adverse cardiovascular events 15 16 . Moreover, Gensini score was an independent predictor of long-term mortality in elderly individuals 17 .…”
Section: Coronary Plaque Featuresdifferences Between Elderly and Youn...mentioning
confidence: 99%
“…In a study by Prajapati et al 15 it was assessed that single vessel disease was more frequent in younger patients and three vessel disease was more prominent in elderly patients. Mahjoob and Yang et al 16,17 also reported in their studies that young adults are characterized by a less extensive coronary disease. Single vessel disease was common in young adults.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 91%